Evolution of a non-condensable gas-entrapped cavitation bubble near the wall via a three-dimensional mesoscopic simulation - Pengfei Xia; Hongke Hao; Xiaolong He; Wanjun Du; Mengqi Huang (Ocean Engineering, 2026)

ScCO2-driven multiscale porosity evolution in coal: Mineral-coupled reconstruction mechanisms and CO2-ECBM implications - Hengyi He; Peng Liu; Baisheng Nie; Xiao Cui; Jingtao Yang; Hao Zhang; Wanjun Chen; Song Bao (Fuel, 2026)

Multiscale Characterization of Anhydrous/Hydrous ScCO2 Effects on Coal: Time-Resolved Mineral-Pore Evolution and Divergent Control Mechanisms - Peng Liu; Wanjun Chen; Jingtao Yang; Baisheng Nie; Hengyi He; Hao Xu; Ang Liu (Gas Science and Engineering, 2026)

Wave characteristics and wave energy resource assessment of the waters bordering China - Yanan Wu; Qingwei Zhou; Wanjun Jiang; Yang Bai; He Wu (Frontiers in Marine Science, 2026)
Wave energy is a clean and renewable marine resource with great development potential. The China Sea, including the Bohai Sea, Yellow Sea, East China Sea and South China Sea, has complex marine conditions. This study aims to clarify the wave characteristics and spatiotemporal distribution of wave energy resources in the China Sea, providing a scientific basis for its rational development and utilization. Using 30-year ERA5 wind field data (1995–2024) as input, the SWAN wave model was adopted to numerically simulate the wave field in the China Sea. The multi-year, seasonal, and monthly average wave and wave ennergy characteristics were analyzed, and wave energy resources was evaluated with wave energy rose diagrams at characteristic points. The Bohai Sea and Yellow Sea had low annual mean wave heights mostly below 1.2 m, the East China Sea 1.2–1.7 m, and high-latitude South China Sea up to 2 m. Most regions except the Bohai Sea and northern Yellow Sea had annual average energy flux densities exceeding 4 kW/m² , especially near Taiwan Island and South China Sea. Wave energy was richest in winter, followed by autumn, and poorest in spring; The characteristic points the dominant direction was east-northeast, with density mainly distributed in 1–10 s wave periods and 0–5 m significant wave heights. The China Sea has substantial wave energy potential. The spatiotemporal and directional characteristics identified provide important references for the design, planning and utilization of wave energy conversion projects in the region.

Dynamic pro-infiltration triggers collapse sinkholes in urban loess roads: Insights from physical and numerical modeling - Kuan Liu; Wanjun Ye; Xueyang Sun; Faning Dang; Mingming He; Xu Duan; Li Wang; Jingjing Nan; Jingyun Gui; Xusheng Yan (Bulletin of Engineering Geology and the Environment, 2026)

Assessing the effect of a non-ionic surfactant on surface degradation of the pesticide Acetamiprid on live tea plants - Wanjun Gao; Xinyi Du; Zili Gao; Haochen Dai; Lanying Li; Bingling Zhang; Gaoxi Wang; Xuejuan Chen; Jeffery Doherty; John M. Clark; Ruyan Hou; Fan Luo; et al. (Food Research International, 2025)

The challenges and progress of CAR-T cell therapy in the treatment of solid tumors - Kai Cui; Wanjun He; Na Huang; Songshan Zhu; Dan Jiang; Weiqiang Yang; Yiwei Zeng; Muhammad Asad Farooq; Guangxian Xu (Molecular and Cellular Biochemistry, 2025)

Anti-osteoporotic effects of peptide PASTGAAK derived from black-boned silky fowl on ovariectomized mice - Yang Qiu; Jiaxin Guo; Jie Zhang; Chenxu Xue; Wanjun He; Jiajin Zhu (Food Bioscience, 2025)

Smartphone app with cloud-based machine learning and visual sensor array for instrument-free detection of species, geographic origin, and quality marker in functional food Gancao - Yun Huang; Aifen Hu; Lixue Ren; WanJun Long; Wei Lan; Yi He; Yuanbin She; Hengye Chen; Haiyan Fu (Food Control, 2025)

No toxic effects or interactions between aflatoxin B1 and zearalenone in broiler chickens fed diets at China's regulatory limits - Wanjun Zhang; Yongpeng Jin; Ying Liu; Ruiqi Tan; Gaoyi Liu; Wenjun He; Sunlin Luo; Yutong Tang; Qiao Chen; Yiqiang Chen (Regulatory Toxicology and Pharmacology, 2025)

Three novel umami peptides from porcine bone hydrolysate and the analysis of the interaction with the Venus flytrap domain of umami taste receptors T1R1/T1R3 - Jie Zhang; Yang Qiu; Jiaxin Guo; Wanjun He; Chenxu Xue; Zixin Wang; Jiajin Zhu (Food Bioscience, 2025)

Role and mechanism of lncRNA ZEB1-AS1 endogenous competition for miR-365a-3p targeting NRF2 in ferroptosis in articular chondrocytes - RenBo Zhang; YuYan Liu; Hui Zang; Axiang He; YanJie Mao; WanJun Liu (Journal of Molecular Histology, 2025)

Abnormal trial-to-trial variability in P300 time-varying directed eeg network of schizophrenia - Chanlin Yi; Fali Li; Jiuju Wang; Yuqin Li; Jiamin Zhang; Wanjun Chen; Lin Jiang; Dezhong Yao; Peng Xu; Baoming He; Wentian Dong (Medical & Biological Engineering & Computing, 2024)

Revealing the mechanisms of water permeability enhancement of urban loess subgrades due to vibration application - Kuan Liu; Wanjun Ye; Xueyang Sun; Faning Dang; Mingming He; Zhao Duan; Jianquan Ma; Jingjing Nan; Ruihui Zheng; Quanjiu Wang (Transportation Geotechnics, 2024)

Appearance, components, pasting, and thermal characteristics of chalky grains of rice varieties with varying protein content - Chenyan He; Fei Deng; Yujie Yuan; Xiaofan Huang; Yuxin He; Qiuping Li; Bo Li; Li Wang; Hong Cheng; Tao Wang; Youfeng Tao; Wei Zhou; et al. (Food Chemistry, 2024)

Effect of sowing date on radiation and temperature use efficiencies of rice in the low-light region of China - Xiaofan Huang; Fei Deng; Chi Zhang; Qiuping Li; Yuxin He; Chenyan He; Xiaofeng Ai; Yujie Yuan; Li Wang; Hong Cheng; Tao Wang; Youfeng Tao; et al. (Field Crops Research, 2024)

A Novel Platinum Resistance-Related Immune Gene Signature for Overall Survival Prediction in Patients with Ovarian Cancer - Chenfei Zhou; Junnan Ma; Wanjun Luo; Jiemei Hu; Jing Chen; Suiying Liang; Shanyang He (Biochemical Genetics, 2024)
Ovarian cancer (OV) is a highly heterogeneous gynecological tumor that makes the prognostic prediction challenging. Resistance to platinum-based chemotherapy is associated with a poor prognosis in OV. There seems to be an overlap between molecular mechanisms responsible for platinum resistance and immunogenicity in OV. However, the predictive role of platinum resistance-related immune genes for OV prognosis needs to be further explored. In our study, the mRNA expression data of OV patients with corresponding clinical information were collected from The Cancer Genome Atlas (TCGA) cohort and International Cancer Genome Consortium (ICGC) cohort. A multigene signature was constructed for OV patients in the TCGA cohort using the least absolute shrinkage and selection operator (LASSO) Cox regression model according to the optimal value of λ and was validated in the ICGC cohort. Furthermore, we performed functional analysis to explore the immune status between low- and high-risk groups based on the median value of the risk score for the multigene signature. Our data showed that there were 41.1% of the platinum resistance-related genes which differentially expressed between immune score low- and high-OV patients in the TCGA cohort. Univariate Cox regression analysis identified 30 differentially expressed genes (DEGs) associated with overall survival (OS) ( P P

Smartphone-based electrochemical sensor for cost-effective, rapid and on site detection of chlorogenic acid in herbs using biomass-derived hierarchically porous carbon synthesized by a soft-hard dual template method - Wanjun Jiang; Zhonghui Zhuo; Xiaohua Zhang; Hai Luo; Lu He; Yuling Yang; Yangping Wen; Zhong Huang; Peng Wang (Food Chemistry, 2024)

Delta like Non-Canonical Notch Ligand 2 inhibits chondrogenic differentiation and cell proliferation of bone marrow mesenchymal stem cells through the Notch1 signaling pathway - Yanan Chen; Yaru Liu; Renbo Zhang; Yanjie Mao; Axiang He; Wanjun Liu (Tissue and Cell, 2023)

Ultra-small magnetic Candida antarctica lipase B nanoreactors for enzyme synthesis of bixin-maltitol ester - Danyu Lv; Muyun Wang; Wanjun He; Jieli Wu; Xiaoyue Liu; Yongguang Guan (Food Chemistry, 2023)

Immunological Markers for Central Nervous System Glia - Hao Huang; Wanjun He; Tao Tang; Mengsheng Qiu (Neuroscience Bulletin, 2023)
Glial cells in the central nervous system (CNS) are composed of oligodendrocytes, astrocytes and microglia. They contribute more than half of the total cells of the CNS, and are essential for neural development and functioning. Studies on the fate specification, differentiation, and functional diversification of glial cells mainly rely on the proper use of cell- or stage-specific molecular markers. However, as cellular markers often exhibit different specificity and sensitivity, careful consideration must be given prior to their application to avoid possible confusion. Here, we provide an updated overview of a list of well-established immunological markers for the labeling of central glia, and discuss the cell-type specificity and stage dependency of their expression.

Rapid detection of adulteration of goat milk and goat infant formulas using near-infrared spectroscopy fingerprints - Yongji He; Wanjun Zeng; Yuxuan Zhao; Xinpeng Zhu; Hongchang Wan; Meng Zhang; Zhicheng Li (International Dairy Journal, 2023)

Short-term exposure to six air pollutants and cause-specific cardiovascular mortality of nine counties or districts in Anhui Province, China - Guoao Li; Huanhuan Zhao; Mingjun Hu; Jialiu He; Wanjun Yang; Hanshuang Zhang; Zhenyu Zhu; Jinliang Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Effects of carbon dioxide and green space on sleep quality of the elderly in rural areas of Anhui Province, China - Guoao Li; Zhenyu Zhu; Mingjun Hu; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Fen Huang (Environmental Science and Pollution Research, 2022)

Six air pollutants and cause-specific mortality: a multi-area study in nine counties or districts of Anhui Province, China - Guoao Li; Huabing Wu; Qi Zhong; Jialiu He; Wanjun Yang; Jinliang Zhu; Huanhuan Zhao; Hanshuang Zhang; Zhenyu Zhu; Fen Huang (Environmental Science and Pollution Research, 2022)

Assessing SARS-CoV-2 RNA levels and lymphocyte/T cell counts in COVID-19 patients revealed initial immune status as a major determinant of disease severity - Mingfeng Han; Mengyuan Xu; Yafei Zhang; Zhongping Liu; Shasha Li; Tengfei He; Jinsong Li; Yong Gao; Wanjun Liu; Tuantuan Li; Zixiang Chen; Xin Huang; et al. (Medical Microbiology and Immunology, 2020)

Spatio-temporal Variation of Soil Respiration and Its Driving Factors in Semi-arid Regions of North China - Xinhua Zeng; Yigang Song; Wanjun Zhang; Shengbing He (Chinese Geographical Science, 2018)

Highly sensitive fluorescence biosensors for sparfloxacin detection at nanogram level based on electron transfer mechanism of cadmium telluride quantum dots - Wanjun Liang; Shaopu Liu; Jing Song; Chenxia Hao; Linlin Wang; Dan Li; Youqiu He (Biotechnology Letters, 2015)